Systematic Review of Studies in the Field of Competencies of New or Soon To BeGraduate General Physicians in Iran - Tahereh Changiz; Mohammad Fakhari; Sepideh Jamshidian; Solmaz Zare; Fariba Asgari (Kerman University of Medical Sciences, 2015)
Background & Objective: One method to evaluate and monitor the effectiveness of the general medicine curriculum is the collection of results of research in this field In this study research results on the extent of predefined general competency in the formal document of the minimum competencies of Iranian general physicians have been systematically integrated   Methods: The search strategy in this study included the searching of words doctor student interns or graduate and ability competency knowledge skill attitude or performance in the title abstract or keywords of articles All papers published from 2002 to 2014 in Persian language journals were retrieved from the Irandoc Iranmedex Magiran Medlib and SID databases   Results: After the removal of irrelevant or duplicate papers from 270 recorded papers 24 articles were selected and analyzed All studies were descriptive studies and most used selfreporting methods to assess the competency of physicians Reviewed articles focused on only 48% of subdomains of the formal document of the minimum competencies of physicians In 70% of assessed skills physicians competencies were estimated as low to moderate   Conclusion: Although these studies did not assess all skills mentioned in the formal document of the minimum competencies of physicians estimates show that the competencies of general physicians in assessed skills were not desirable It is recommended that future studies in this field to be managed